Muscle fatigue in males and females during multiple-sprint exercise - Billaut, F.; Bishop, D. (Sports Medicine, 2009)
Females have often been reported to have a greater muscle fatigue resistance than males, especially during exercise at low-to-moderate intensities. Differences in muscle mass, muscle metabolism and voluntary activation patterns have been the primary explanations for the differences in performance and physiological responses to exercise between sexes. However, while ample data are available for isometric contractions, dynamic activity is a less studied mode of exercise, and there is even less information regarding multiple-sprint exercise (MSE). This is surprising given that MSE places unique demands on metabolic processes in the muscle where energy supply oscillates between fuelling contractile activity and restoring homeostasis. As such, MSE provides a rich area for future applied research. This review examines the limited data available concerning the physiological responses of males and females to sprint exercise, and discusses the methodological confounds arising from non-appropriate comparison methods. Based on original findings, we highlight that sex differences in the absolute mechanical work performed during a given task might explain a significant part of the differences in physiological responses of males and females to sprint exercise. We therefore suggest that future studies using male and female subjects to answer basic physiological questions use mechanical work as a covariate.